Surface‐expressed insulin receptors as well as IGF‐I receptors both contribute to the mitogenic effects of human insulin and its analogues. Issue 7 (21st November 2014) - Lundby, Anders; Bolvig, Pernille; Hegelund, Anne Charlotte; Hansen, Bo F.; Worm, Jesper; Lützen, Anne; Billestrup, Nils; Bonnesen, Christine; Oleksiewicz, Martin B.
Abstract There is a medical need for new insulin analogues. Yet, molecular alterations to the insulin molecule can theoretically result in analogues with carcinogenic effects. Preclinical carcinogenicity risk assessment for insulin analogues rests to a large extent on mitogenicity assays in cell lines. We therefore optimized mitogenicity assay conditions for a panel of five cell lines. All cell lines expressed insulin receptors (IR), IGF‐I receptors (IGF‐IR) and hybrid receptors, and in all cell lines, insulin as well as the comparator compounds X10 and IGF‐I caused phosphorylation of the IR as well as IGF‐IR. Insulin exhibited mitogenicity EC50 values in the single‐digit nanomolar to picomolar range. We observed correlations across cell types between (i) mitogenic potency of insulin and IGF‐IR/IR ratio, (ii) Akt phosphorylation and mitogenic potency and (iii) Akt phosphorylation and IR phosphorylation. Using siRNA‐mediated knockdown of IR and IGF‐IR, we observed that in HCT 116 cells the IR appeared dominant in driving the mitogenic response to insulin, whereas in MCF7 cells the IGF‐IR appeared dominant in driving the mitogenic response to insulin. Together, our results show that the IR as well as IGF‐IR may contribute to the mitogenic potency of insulin. While insulin was a more potent mitogen than IGF‐I in cells expressing more IR than IGF‐IR, the hyper‐mitogenic insulin analogue X10 was a more potent mitogen than insulin across all cell types, supporting that the hyper‐mitogenic effect of X10 involves the IR as well as the IGF‐IR. These results are relevant for preclinical safety assessment of developmental insulin analogues. Copyright © 2014 John Wiley & Sons, Ltd.